2015
DOI: 10.3892/ol.2015.3748
|View full text |Cite
|
Sign up to set email alerts
|

Pro-apoptotic and anti-proliferative effects of mitofusin-2 via PI3K/Akt signaling in breast cancer cells

Abstract: Abstract. The mitochondrial GTPase mitofusin-2 (Mfn2) gene is a novel gene characterized as a cell proliferation inhibitor. Mfn2 has previously been reported to play a role in regulating cell proliferation, apoptosis and differentiation in a number of cell types. However, there are no studies on the effect of Mfn2 in breast cancer. In this study, we aimed to elucidate the function and mechanism of Mfn2 in breast cancer. A plasmid encoding the complete Mfn2 open reading frame (pEGFP-Mfn2) was used to infect bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 25 publications
3
25
0
Order By: Relevance
“…Hence, the single loss of Mfn1 might have enhanced MFN2 activity, with potential deleterious consequences such as those observed in Mfn1 ‐cKO oocytes. In support of this notion, previous reports have shown that MFN2 inhibits the PI3K‐Akt signaling 17,56‐59 . In addition, overexpression of MFN2, but not MFN1, impairs ER redistribution and results in a severe loss of Ca 2+ stores in oocytes 5 .…”
Section: Discussionmentioning
confidence: 57%
“…Hence, the single loss of Mfn1 might have enhanced MFN2 activity, with potential deleterious consequences such as those observed in Mfn1 ‐cKO oocytes. In support of this notion, previous reports have shown that MFN2 inhibits the PI3K‐Akt signaling 17,56‐59 . In addition, overexpression of MFN2, but not MFN1, impairs ER redistribution and results in a severe loss of Ca 2+ stores in oocytes 5 .…”
Section: Discussionmentioning
confidence: 57%
“…24) Furthermore, bavachin was reported to exhibit direct effect on Akt phosphorylation. 11,57) In this study, we showed that Mfn2 ablation by the siRNA resulted in the inhibition of phosphor-Akt, and inhibition of phosphorAkt also aggravated bavachin-induced ER stress (Fig. S1).…”
Section: Discussionmentioning
confidence: 95%
“…PI3K/Akt signaling pathway is aberrant in a wide variety of cancers and has been shown to play a central role in cancer cell proliferation, migration, invasion, and apoptosis [15][16][17]. Downstream effectors of AKT are involved in survival, growth and metabolic-related pathways [18].…”
Section: Discussionmentioning
confidence: 99%